A Review of Different Models Derived from Classical Kolmogorov, Johnson and Mehl, and Avrami (KJMA) Theory to Recover Physical Meaning in Solid‐State Transformations. Issue 6 (18th March 2022) - Blázquez, Javier S.; Romero, Francisco J.; Conde, Clara F.; Conde, Alejandro
Abstract : The classical theory of solid‐state transformation based on nucleation and growth processes, developed by Kolmogorov, Johnson and Mehl, and Avrami (KJMA theory), is widely used in many different fields of research. In KJMA theory, two parameters (the frequency factor and, particularly, the Avrami exponent) can supply information about the mechanisms involved in the transformation. Despite its apparent simplicity, on the one hand, the results derived from this theory can be strongly affected by the indetermination of experimental data (e.g., onset of the transformation). On the other hand, KJMA theory is developed for isothermal polymorphic transformations in which randomly distributed nuclei grow in convex shapes. However, several procedures have extended KJMA theory to nonisothermal regimes and to many different processes deviating from those premises. Herein, the requirements of KJMA theory and the expected deviations for these approximations are briefly discussed. In addition, some strategies are proposed for recovering physical meaning from the effective parameters deduced in several transformations including nanocrystallization and martensitic transformations for which results can be interpreted under the approximation of instantaneous growth. Abstract : The broadly used Kolmogorov, Johnson and Mehl, and Avrami (KJMA) kinetic theory is more restricted than the numerous cases to which it is applied. Understanding these restrictions allows users to interpret whether a physical meaning is straightforward or not.